Inclusion effect of jack mackerel meal in diets substituting fish meal with corn gluten meal on growth and feed utilization of olive flounder (Paralichthys olivaceus) - Islam, Md. Rabiul; Cho, Sung Hwoan; Kim, Taeho (Frontiers in Sustainable Food Systems, 2024)
Inclusion effect of different amount of jack mackerel meal (JMM) in the diets substituting 50% fish meal (FM) with corn gluten meal (CGM) on growth, feed availability, biochemical composition, plasma, and serum chemistry of olive flounder (Paralichthys olivaceus) was elucidated. Seven experimental diets were formulated. The control (Con) diet contained 60% FM. Fifty percent of FM in the Con diet was substituted with CGM, and then 5, 10, 20, 30, 40, and 50% JMM were added at the expense of FM to formulate the CJ5, CJ10, CJ20, CJ30, CJ40, and CJ50 diets, respectively. All formulated feeds were assigned to triplicate groups of fish. A total of 420 juvenile fish averaging 18 ± 0.01 g (mean ± SEM) was uniformly divided into 21, 50-L tanks, with 20 fish per tank. Fish were carefully hand-fed to satiation for 8 weeks. The weight gain of olive flounder fed the Con diet was significantly (p < 0.001) higher than that of fish fed the CJ5, CJ10, and CJ20 diets, but not significantly (p > 0.05) different from that of fish fed the CJ30, CJ40, and CJ50 diets. Olive flounder fed the Con diet achieved significantly (p < 0.001 and p < 0.04) greater specific growth rates (SGR) and feed consumption than those of fish fed the CJ5 and CJ10 diets, but not significantly (p > 0.05) different from those of fish fed the CJ20, CJ30, CJ40, and CJ50 diets. However, there were no significant (p > 0.05) differences in feed utilization, proximate composition, amino acid profiles, and plasma and serum parameters of olive flounder. In conclusion, incorporation of 30, and 20% JMM are the most desirable treatments in the olive flounder diets replacing 50% FM with CGM based on weight gain, and SGR and feed consumption, respectively. This study will be very helpful to develop low-FM diets for sustainable olive flounder culture.